The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/chin.200945033
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Aerobic Photooxidative Cleavage of the C—C Double Bonds of Styrenes.

Abstract: Oxidation O 0212Aerobic Photooxidative Cleavage of the C-C Double Bonds of Styrenes.αor β-Substituted styrenes, which show low reactivity under previoulsy reported cleavage conditions, are converted into the corresponding benzoic acids and ketenes using carbon tetrabromide as catalyst under aerobic photo-irradiation conditions. -(HIRASHIMA, S.-I.; KUDO, Y.; NOBUTA, T.; TADA, N.; ITOH*, A.; Tetrahedron Lett. 50 (2009) 30, 4328-4330; Gifu Pharm. Univ., Mitahora, Gifu 502, Japan; Eng.) -Mais 45-033

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…First, we screened the bromine sources and solvents in the presence of molecular oxygen under photoirradiation from a 400 W mercury lamp (Table 1, entries [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Benzoic acid (2a) was produced most efficiently albeit in moderate yields when using CBr 4 as catalyst and ethyl acetate as solvent ( Table 1, entry 1).…”
Section: Scheme 1 Aerobic Oxidative Cleavage Of Alkynesmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we screened the bromine sources and solvents in the presence of molecular oxygen under photoirradiation from a 400 W mercury lamp (Table 1, entries [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Benzoic acid (2a) was produced most efficiently albeit in moderate yields when using CBr 4 as catalyst and ethyl acetate as solvent ( Table 1, entry 1).…”
Section: Scheme 1 Aerobic Oxidative Cleavage Of Alkynesmentioning
confidence: 99%
“…10 In the course of further studying this reaction, we found that the oxidative cleavage of the carbon-carbon triple bonds occurred in the presence of catalytic amounts of carbon tetrabromide (CBr 4 ) and water under aerobic photoirradiation conditions (Scheme 1). We report herein a detailed study of this photooxidative cleavage of alkynes.…”
mentioning
confidence: 98%
See 1 more Smart Citation